A simulation based performance analysis of reactive routing protocols in Wireless Mesh Networks - Rahman, Md. Arafatur; Azad, Md. Saiful; Anwar, Farhat; Hassan Abdalla Hashim, Aisha (2009)
Wireless Mesh Networks (WMNs) have recently gained a lot of popularity due to their rapid deployment and instant communication capabilities. WMNs are dynamically self- organized, self-configured and self-healed, with the nodes in the network automatically establishing an ad hoc network and preserving the mesh connectivity. Due to the increasing intereston wireless mesh architectures, a new IEEE working group, 802.11s has recently created. The purpose of this working group is to standardize the architectures and protocols that support both broadcast/multicast and unicast delivery between Access Points (APs). In this paper, a detailed simulation based performance study and analysis is performed on the reactive routing protocols over such kind of networks. Ad Hoc On-Demand Distance Vector (AODV), Dynamic Source Routing (DSR) and Dynamic MANET On-demand (DYMO) routing protocol are considered as the representative of reactive routing protocols. The performance differentials are investigated using varying traffic load and number of source. Based on the simulation results, how the performance of each protocol can be improved is also recommended.